2011
DOI: 10.1371/journal.pone.0025423
|View full text |Cite
|
Sign up to set email alerts
|

Altered Topological Properties of Functional Network Connectivity in Schizophrenia during Resting State: A Small-World Brain Network Study

Abstract: Aberrant topological properties of small-world human brain networks in patients with schizophrenia (SZ) have been documented in previous neuroimaging studies. Aberrant functional network connectivity (FNC, temporal relationships among independent component time courses) has also been found in SZ by a previous resting state functional magnetic resonance imaging (fMRI) study. However, no study has yet determined if topological properties of FNC are also altered in SZ. In this study, small-world network metrics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
110
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 129 publications
(113 citation statements)
references
References 91 publications
1
110
2
Order By: Relevance
“…2008; Yu et al. 2011) in patients with psychotic disorder compared to healthy controls. Of note, the sample size of this study ( N  = 228) was considerably higher compared to other studies ( N  < 62).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…2008; Yu et al. 2011) in patients with psychotic disorder compared to healthy controls. Of note, the sample size of this study ( N  = 228) was considerably higher compared to other studies ( N  < 62).…”
Section: Discussionmentioning
confidence: 98%
“…However, a previous graph theoretical study found an association between negative symptoms and different topological properties (i.e., characteristic path length and global efficiency) which was not observed in this study (Yu et al. 2011). These inconsistencies may be due to the analyzing techniques used by the two studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations